Antioxidant and antibacterial activities of hydroalcoholic extracts from aloysia polystachya griseb moldenke and lippia turbinata griseb (Verbenaceae) - Aguado, María Inés (2016)
Objective: The aims of this study were to determine polyphenols and flavonoids composition, to evaluate the antioxidant and antibacterialactivities and possible antibacterial synergistic effects of hydroalcoholic extracts of Aloysia polystachya and Lippia turbinata.Methods: The flavonoids analysis was carried out in ethyl acetate fractions by means of high-performance liquid chromatography coupled toelectrospray ionization quadrupole time of flight mass spectrometry (HPLC-ESI-Q-TOF-MS). The phenolic content was measured using FolinCiocalteu reagent. The 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical method was used to estimate the antioxidant capacity. The antibacterialactivity was determined by theantibacterial synergism.Results: Several flavonoid compounds were detected for the first time in these species, being Lippia turbinata extract the one that presented thehighest total phenolic content and antioxidant activity.employed in this work. The extract combinations had a synergistic effect against three bacteria, one of them Gram-negative.Conclusion: These extracts have demonstrated antioxidant and antibacterial activity, and its combination showed a synergistic effect againstmethicillin-resistant Staphylococcus aureus. Biological activities would be attributed to the whole of phytochemical constituents present in therespective crude extracts. However, it could be considered that the found flavonoids play an important roleagar microdilution and broth microdilution methods. The checkerboard assay was carried out to determine possibleExtracts from both species would have bactericidal activity against Staphylococcus strainsin the development of these activities.